Juliet Dove, Queen of Love - Coville, Bruce (Orlando, Fla. : Magic Carpet Books, 2005)
A shy twelve-year-old girl must solve a puzzle involving characters from Greek mythology to free herself from a spell which makes her irresistible to boys.
"A Magic shop book."
School Library Journal
Wilson's Children
Wilson's Junior High School
5.3
3-6.
Keywords: Bashfulness -- Fiction; Magic -- Fiction; Mythology, Greek -- Fiction; Greek mythology -- Fiction; Magic -- Fiction; Shyness -- Fiction